Rapid and punctuated Late Holocene recession of Siling Co, central Tibet. (15th September 2017) - Shi, Xuhua; Kirby, Eric; Furlong, Kevin P.; Meng, Kai; Robinson, Ruth; Lu, Haijian; Wang, Erchie
Abstract: Variations in the strength of the Asian monsoon during Holocene time are thought to have been associated with widespread changes in precipitation across much of Tibet. Local records of monsoon strength from cave deposits, ice cores, and lake sediments typically rely on proxy data that relate isotopic variations to changes in precipitation. Lake expansion and contraction in response to changing water balance are likewise inferred from sedimentologic, isotopic and paleobiologic proxies, but relatively few direct records of changes in lake volume from preserved shorelines exist. Here we utilize relict shoreline deposits and associated alluvial fan features around Siling Co, the largest lake in central Tibet, to reconstruct centennial-to-millennial-scale variations in lake area and volume over the Holocene. Mapping and surveying of lacustrine shorelines coupled with optically stimulated luminescence dating of associated deposits indicate protracted occupation of a highstand elevation from >8 ka to 4 ka, followed by rapid recession that was likely punctuated by several stillstands of centennial-scale duration. Calculation of the changes in lake surface area and past hydrologic indices of the Siling Co basin suggests the effective moisture during the early Holocene highstand was approximately three times greater than today. In contrast to other lakes in central and western Tibet, our results suggest that Siling Co did not begin to recede synchronously with decreasing solar insolation at ca. 9–8 ka. Rather, initial recession of Siling Co appears to correspond to a time period of enhanced aridity and weakened monsoon in both Africa and Asia at ca. 4.2 ka. Our results add to a growing body of literature that suggest a period of relatively severe aridity on the Tibetan Plateau at this time. We suggest that subsequent punctuated recession of Siling Co was punctuated by similar periods of abrupt climate change during the Late Holocene. Graphical abstract: Highlights: Early Holocene highstand of Siling Co occurred >8–4 ka. Rapid recession of Siling Co appears to have initiated at ca. 4 ka. Lake recession was punctuated by 3 centennial-length still-stands since 4 ka. The hydrologic index prior to 4 ka was substantially greater than today.